Knowledge Readiness of Head Teachers to Implement Inclusive Education Policies for Learners with Visual Impairments in Primary Schools of the North West Region of Cameroon - Nkumson, Comfort Harpseh; Ngalim , Valentine Banfegha; Ngwa , Emmanuel Shu (American Journal of Education and Practice, 2024)
Purpose: This study investigated the Knowledge readiness of head teachers to implement inclusive education policies for learners with visual impairments in primary schools in the North West Region of Cameroon. Given that inclusion, equity and social justice are emerging trends in education, there is need for headteachers and teachers to be ready to change the quality of services they offer in school. The main purpose of this study was: to find out how ready head teachers are in terms of knowledge of inclusive education legislation and its effect on inclusive education practices for learners with visual impairments in primary schools. Materials and Methods: Methodology adopted was a mixed research approach, a sequential explanatory design was used in the study, both probability and non-probability sampling techniques were employed to sample a population of 374 teachers and head teachers from different primary schools in divisions of the North West Region of Cameroon. The research instruments were questionnaire and interview guide and the data was analysed using SPSS version 20, while qualitative data was analyzed thematically. Data were presented on tables and charts using frequencies, mean, standard deviation and levels of significance. Findings: Findings brought to light that, 56.7% of head teachers have knowledge on inclusive education legislation, 45% of teachers have knowledge on inclusive education legislation and knowledge on inclusive education legislation has a significant effect on inclusive education practices for learners with visual impairments in primary schools at the level of significance of 0.000. Implications to Theory, Practice and Policy: From these findings recommendations were made to the government for teacher training to be made inclusive and provide continuous professional development and capacity building for teacher, also financial and material supported should be provided for implementation of inclusive education as stated in the policies.